Platelet-to-lymphocyte ratio for prognostication in immune checkpoint inhibitor-treated cancer patients: a meta-analysis of 13027 patients highlighting nivolumab-responsive renal cell carcinoma - Wang, Mingxing; Dong, Wanhui; Chen, Jian; Wu, Pantong; Wang, Yuru; Zhang, Xiaonan; Cao, Yaning; Wang, Zhiying; Zhong, Zhixian; Zhong, Yi (Frontiers in Immunology, 2026)
ObjectiveTo assess platelet-to-lymphocyte ratio (PLR) prognostic utility for overall (OS) and progression-free survival (PFS) in immune checkpoint inhibitor-treated cancer patients, and examine impacts of geography, cancer type, cutoff, ICI class, treatment line and stage.MethodsA systematic literature search identified studies investigating PLR and prognosis in ICI treated patients. Hazard ratios (HRs) with 95% confidence intervals (CIs) were pooled using random-effects models. Subgroup analyses examined key covariates; publication bias was assessed.ResultsAnalysis of 98 publications (86 OS, 72 PFS) demonstrated that elevated PLR was a robust predictor of shorter OS (HR 1.79, 95% CI: 1.60-2.00) and PFS (HR 1.60, 95% CI: 1.44-1.78). Subgroup analyses revealed: (1) Geographic region: Asian populations exhibited the most consistent correlation with OS and the highest PFS risk (69%). (2) Cancer type: For OS, prognostic value was maintained across all cancers; the most pronounced impacts were observed in hepatocellular carcinoma (HR 2.10), esophageal carcinoma (HR 2.08), and head and neck squamous cell carcinoma (HR 2.61). For PFS, a notable link to poor outcomes was observed in NSCLC and hepatocellular carcinoma, whereas renal cell carcinoma showed no such correlation. (3) PLR cutoff: both PLR ≥180 (OS: HR 1.87; PFS: HR 1.68) and PLR <180 (OS: HR 1.73; PFS: HR 1.53) subgroups consistently yielded unfavorable outcomes. (4) ICI category: for OS, camrelizumab showed the strongest prognostic relevance (HR 4.68), whereas for PFS, all ICIs yielded consistent results. (5) Treatment line: both first-line (OS: HR 1.98; PFS: HR 1.93) and second-line or beyond (OS: HR 1.87; PFS: HR 1.79) demonstrated clear prognostic utility without inter-subgroup differences. (6) Tumor stage: Advanced stages (III–IV, IIIB–IV, IV) confirmed the predictive value of PLR for both OS and PFS. (7) Cancer Subtypes: PLR remained prognostic in nivolumab-treated, stage IV genitourinary cancers; correlated with survival in pembrolizumab-treated but not nivolumab-treated NSCLC; and remained predictive in camrelizumab-treated/advanced gastrointestinal tumors. Notably, elevated PLR was uniquely associated with worsened OS and PFS in nivolumab-treated renal cell carcinoma.ConclusionsElevated PLR is consistently associated with shortened OS across the cancer types receiving ICIs, while its prognostic value for PFS fluctuates depending on cancer type and ICI class. The prognostic impact of PLR is particularly robust in the nivolumab-treated RCC, pembrolizumab-treated NSCLC, camrelizumab-treated gastrointestinal tumors, and various advanced-stage malignancies.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/.